Investigating the present vegetation to understand the past one: “modern analogues” in the Sultanate of Oman - Bellini, Cristina; Baldini, Riccardo Maria; Gonnelli, Tiziana; Lippi, Marta Mariotti (Webbia, 2015)
The study of the present-day pollen rain in modern sites reveals the relationship between vegetation and relative pollen spectra, and provides a useful key for the interpretation of the past pollen records resulting from palaeoenvironmental researches. The modern sites, or “modern analogues”, are accurately selected and considered paradigmatic models. In this paper the first results of two archaeobotanical studies carried out in two different areas of the Sultanate of Oman are presented: Salut (northern Oman) and the ancient town of Sumhuram (southern Oman, Dhofar).
Keywords: Botanique – Oman